AB0004 Collagen-specific tcr repertoire usage in rheumatoid arthritis and cytokine secretion. (23rd January 2014) - Fedele, A. L.; Di Sante, G.; Nicolò, C.; Tolusso, B.; Carbonella, A.; Gigante, M. R.; Bosello, S. L.; Gremese, E.; Canestri, S.; Ria, F.; Ferraccioli, G.
Abstract : Background: We have previously reported the characterization of the TCR-beta chain repertoire of T cells specific for Human Collagen II p261-273 in DR4+ RA patients and DR4+healthy controls (1 ). Objectives: We observed that it is possible to identify a limited number of TCR-beta chain recurrently used in patients during the acute presentation of the disease, as opposed to the same patients after disease amelioration, versus healthy control subjects. We could also show that a part of this repertoire is spontaneously enriched in the Synovial fluid. Methods: We examined the usage of the two more commonly used TCR-beta chains (BV11 and BV13) in 85 consecutive samples from RA patients of various HLA DR haplotype (25 DR4+, 13 DR1+, 11 DR7+ and 37 of other haplotypes; one patient was DR4+ DR1+) at acute presentation (47) or remission (38) of disease. Peripheral Blood Mononuclear Cells (PBMC) were isolated, cultured in the absence or presence of collagen peptide and examined by immunoscope, as described. In addition, we examined the ability of collagen-specific individual T cells of 3 DR4+ patients to secrete IL-17 and IL-13 upon stimulation in vitro with the peptide, in the absence or presence of bacteria-derived products, following the method recently described (2 ). Results: Confirming the previously reported observations, 40 (6/15) and 50 (7/15)% of RA patients in acute disease display the presence of BV11+ or BV13+ T cells. Pooling patients positive for either or both TCRs, the frequency of positive samples increased only to 8/16. The frequency of the same T cells in the collagen-specific repertoire residual after induction of remission decreases to 1/11 and 2/10, respectively. Two more groups of RA patients displayed collagen-specific T cells using similar BV11 and BV13 beta chains, namely DR1+ patients (2/9 in each case) and DR7+ patients (3/6 in each case). In the case of DR7+ patients, however, the frequency of positive samples did not decrease following remission of symptoms. Three out of 18 patients with other haplotypes showed usage of BV11+ cells and 1/19 used BV13+ cells. We examined the ability of a total of 17 individual T cells from 3 DR4+patients (1 in acute disease and 2 in remission) to secrete IL-17 and IL-13. When PBMC were stimulated in the presence of peptide only, just 1 T cells was able to secrete IL-17 and 1 IL-13, both observed in the patient in acute disease. However, when stimulation with the peptide was associated with the presence of bacterial products, 3 more individual T cells became able to secrete IL-17. Conclusions: We confirm that BV11 and BV13+ cells are bystander of the acute presentation of the disease in DR4+ patients. The relative high frequency of usage of these clonotipic TCRs in DR1+ and DR7+ patients is possibly due to the similarities in presentation of the antigen between these DR alleles. The secretion of the highly pro-inflammatory cytokine IL-17 is modulated by endogenous or exogenous factors (possibly interacting with PRRs) which may thereby influence the severity of local damage. References: Ria F et al, Arth Res Ther 2008, 10:R135. Nicolò C et al, J Immunol 2010, 184:222-235. Disclosure of Interest: None Declared